Tantangan dan Prospek Studi Bahasa Arab di Indonesia - Abdul Munip (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2019)
Abstract In fact, Arabic in Indonesia has been studied since Islam entered Indonesia, because Arabic is the language of two main sources of Islamic teachings, and is also used in the rituals of prayer, dhikr and prayer. Religious motivation is the most significant why Arabic is still studied in Indonesia until now. However, learning Arabic in Indonesia has not shown brilliant success, especially in the four language skills comprehensively. This article aims to explore the challenges and prospects of studying Arabic in Indonesia. Currently, Arabic studies are facing challenges, among others: first in terms of objectives. There is confusion between learning Arabic as a goal, namely mastering language proficiency, and learning Arabic as a tool for mastering other knowledge that uses Arabic as its source. Second, in terms of the types of Arabic that are studied, whether classical Arabic, modern or everyday Arabic. Third in terms of the method, there is uncertainty between maintaining the old method and using the new method. Linguistic and non-linguistic problems also play a role in disrupting the smooth study of Arabic for Indonesian students. However, all of that did not reduce the enthusiasm of Indonesians in learning Arabic. This is proven by the establishment of Arabic Language Study Program in several universities. Learners of Arabic also don't need to worry, because the translating profession can become their career choice Keywords: Arabic Language Challenges, Arabic Prospects, Arabic Studies. Abstrak Sesungguhnya, bahasa Arab di Indonesia telah dipelajari sejak Islam masuk ke Indonesia, karena bahasa Arab adalah bahasa yang digunakan dalam dua sumber utama ajaran Islam, dan juga digunakan dalam ritual shalat, berdzikir dan berdoa. Motivasi religius menjadi motivasi paling signifikan mengapa bahasa Arab masih dipelajari di Indonesia sampai sekarang ini. Namun demikian, pembelajaran bahasa Arab di Indonesia belum menunjukkan kesuksesan yang gemilang, terutama dalam penerapan empat kemahiran secara komprehensif. Artikel ini bertujuan mengeksplorasi tantangan dan prospek studi bahasa Arab di Indonesia. Sesunguhnya, sekarang ini studi bahasa Arab sedang menghadapi tantangan antara lain: pertama dari segi tujuan. Terdapat kerancuan antara mempelajari bahasa Arab sebagai tujuan, yakni menguasai kemahiran berbahasa, dan mempelajari bahasa Arab sebagai alat untuk menguasai pengetahuan lain yang menggunakan bahasa Arab sebagai wahananya. Kedua dari segi jenis bahasa Arab yang dipelajari, apakah bahasa Arab klasik, modern atau bahasa Arab sehari-hari. Ketiga dari segi metode, terdapat kegamangan antara mempertahankan metode lama dan menggunakan metode baru. Problem linguistik dan non linguistik juga berperan dalam mengganggu kelancaran studi bahasa Arab untuk siswa Indonesia. Namun demikian, semua itu tidak mengurangi semangat orang Indonesia dalam mempelajari bahasa Arab. Hal ini dibuktikan dengan berdirinya prodi Pendidikan Bahasa Arab di beberapa perguruan tinggi. Para pembelajar bahasa Arab juga tidak perlu khawatir, karena profesi penerjemah bisa menjadi pilihan karier mereka. Kata Kunci: Tantangan Bahasa Arab, Prospek Bahasa Arab, Studi bahasa Arab